CREDIBILITY AND SEARCH ENGINES. THE EFFECTS OF SOURCE REPUTATION, NEUTRALITY AND SOCIAL RECOMMENDATIONS ON THE SELECTION OF SEARCH ENGINE RESULTS - Unkel, Julian; Haas, Alexander (AoIR Selected Papers of Internet Research, 2015)
This paper examines factors influencing the selection of search engine results. Scholars argue that to avoid getting exposed to wrong or even harmful information, credibility evaluation of online content becomes a “core component” for the recipients. We therefore analyze whether credibility attributions are also able to influence recipients’ selection decisions. We compare the effects of the search results’ position on the SERP to those of three credibility cues (source reputation, message neutrality, and social recommendations). The results of our study (n = 247) suggest a secondary role of credibility in selection processes. Most people rely on the given ranking: the higher the result is ranked, the more likely it is selected. An additional effect is only found for reputation, showing that high reputation results are more likely to be selected. This would mean that either search engine users might not be aware that the assessment of the quality of information should be a core concern to them and seem to trust the given ranking rather uncritically, or that they indeed assess the credibility of information sources very well, but that this assessment is guided largely by their imaginary of search engines as providing the best results on top.